Investigating the characterization, kinetic mechanism, and thermodynamic behaviour of coal-biomass blends in co-pyrolysis process - Hamad Gohar (00000318657); Dr. Asif Hussain Khoja (USPCAS-E, NUST, Islamabad, 2022)
TH-363
Keywords: MS-TEE Thesis MS Thesis